RISK PERCEPTION AND INTENTION OF TOURING TO THE CITY OF SABANG IN THE TIME OF THE COVID-19 PANDEMIC - Munandar, Munandar; Chalirafi, Chalirafi; Bachri, Naufal; Fuadi, Fuadi; Syauki, Moh. (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2021)
The purpose of this study was to determine the impact of the risk perception of tourists on the intention to travel to Sabang City in the midst of the Covid 19 pandemic. This research is based on the theoretical framework of the theory of planned behavior (TPB). Sample approach using Non-Probabilityaccidental sampling.The sample amounted to 200 respondents who came from within and outside the province of Aceh. The results of this study indicate that the perception of risk has a negative and significant effect on the antecedents of Intention, namely Attitude, Behavioral Control, and Subjective Norms. Attitudes and Behavioral Control each have a positive and significant effect on the intention of tourists visiting Sabang City during the covid 19 pandemic. Meanwhile, Subjective Norms have no significant effect.